Análise de viabilidade econômica de um gerador em horário de ponta em uma cerealista - Limberger, Karoline Parsianello (2018)
The consumption of electricity is one of the most worrisome issues of the present day, due to the increase of its demand and the limitations faced in the supply. The present work presents an economic feasibility study, of the installation of a diesel generator as an alternative source of energy generation at peak hours in a cerealist, in which the cost of energy is higher. In this context, data on energy consumption during peak hours were collected by the company over a period of approximately one year to determine whether, in addition to supplying the required demand, it could also provide security for possible supply problems by the concessionaire. From this, an economic feasibility study of the Investment Project (PI) was carried out, using the Multi-Indexed Expanded Methodology (MMIA) in the web application $ AVEPI, allowing to analyze the return and risk indicators of the Multi-index Methodology (MMI), and Limit Values (VLs) and Elasticity Limits (SLs), through the sensitivity analysis. The investment project (IP) had a higher return potential if the company invested with equity, even though the TMA was low, and the low-medium risk.